Cost-effectiveness Analysis of Ribociclib plus Letrozole versus Palbociclib plus Letrozole in the United Kingdom - Gaurav Suri; David Chandiwana; Adam Lee; Rohit Mistry (Journal of Health Economics and Outcomes Research, 2019)
# Objective To evaluate the cost-effectiveness of ribociclib plus letrozole versus palbociclib plus letrozole in post-menopausal women with hormone receptor positive (HR+) and human epidermal growth receptor 2 negative (HER2-) advanced breast cancer from a UK payer perspective.